a) x3 +x+2
=\(\left(x^3+x^2\right)-\left(x^2+x\right)+\left(2x+2\right)\)
=\(\left(x+1\right)\left(x^2-x+2\right)\)
b) x3-2x-1
=\(\left(x^3+x^2\right)-\left(x^2+x\right)-\left(x+1\right)\)
=\(\left(x+1\right)\left(x^2-x-1\right)\)
c) x3+3x2-4
=\(\left(x^3-x^2\right)+\left(4x^2+4x\right)-\left(4x+4\right)\)
=\(\left(x-1\right)\cdot\left(x^2+4x-4\right)\)
d) x3+3x2y-9xy2+5y3
=\(\left(x^3-x^2y\right)+\left(4x^2y-4xy^2\right)-\left(5xy^2-5y^3\right)\)
=\(\left(x-y\right)\left(x^2+4xy-5y^2\right)\)
=\(\left(x-y\right)^2\left(x-5y\right)\)
a)
\(x^3+x+2\)
\(=\left(x^3+x^2\right)-\left(x^2+x\right)+\left(2x+2\right)\)
\(=x^2\left(x+1\right)-x\left(x+1\right)+2\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-x+2\right)\)
b)
\(x^3-2x-1\)
\(=\left(x^3+x^2\right)-\left(x^2+x\right)-\left(x+1\right)\)
\(=x^2\left(x+1\right)-x\left(x+1\right)-\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-x-1\right)\)
c)
\(x^3-3x^2-4\)
\(=\left(x^3-x^2\right)+\left(4x^2-4x\right)+\left(4x-4\right)\)
\(=x^2\left(x-1\right)+4x\left(x-1\right)+4\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2+2.2.x+2^2\right)\)
\(=\left(x-1\right)\left(x+2\right)^2\)
d)
\(x^3-3x^2y-9xy^2+5y^3\)
\(=\left(x^3-x^2y\right)+\left(4x^2y-4xy^2\right)-\left(5xy^2-5y^3\right)\)
\(=x^2\left(x-y\right)+4xy\left(x-y\right)-5y^2\left(x-y\right)\)
\(=\left(x-y\right)\left(x^2-4xy-5y^2\right)\)
\(=\left(x-y\right)^2\left(x-5y\right)\)